Stator grounding fault severity characterization and novel inverse-time protection method for large generators - Yikai Wang; Jie Ou; Jian Qiao; Zengping Wang; Xianggen Yin; Chunguang Ren (International Journal of Electrical Power & Energy Systems)
The existing injection-type stator grounding protection schemes for large generators are configured to issue only an alarm signal under high transition resistance grounding fault conditions. Thus, the fault cannot be promptly cleared. And it leads to continuous accumulation of fault arc energy, which may severely damage the stator iron core and winding insulation. The energy generated by the fault arc continues to accumulate in severe cases, causing damage to winding insulation and the stator iron core. The fault arc energy cannot be directly measured or calculated, but it is proportional to the fault arc power. Thus, the grounding fault severity is characterized by the fault arc power in this paper, and a real-time fault arc power calculation method is proposed. On this basis, a novel inverse-time grounding fault protection method for large generators according to the fault arc power is constructed. Experiment results show that the proposed fault arc power calculation method based on the slot potential analysis unit is accurate, with an error margin of less than 0.5 %. Simulation results show that the proposed protection method limits the fault arc damage to a “slight” level. Thus, the generator’s safety under high transition resistance grounding fault conditions can be guaranteed.